Student Development Management in Increasing Social Awareness of the Community at Sumbersari 2 State Elementary School Malang - Wahyudi Widodo (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Student development management is a crucial aspect of primary education aimed at shaping students’ character, particularly in fostering social awareness within the community. However, several issues remain in practice, including low levels of empathy among students, a tendency toward individualistic behavior, and the suboptimal management of school development programs. This study aims to analyze student development management in enhancing social awareness at Sumbersari 2 State Elementary School Malang, focusing on planning, implementation, and evaluation. A qualitative approach with a descriptive design was employed. Data were collected through observation, interviews, and documentation involving the principal, teachers, students, and parents as research subjects. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while validity was ensured through triangulation techniques. The findings reveal that student development management was implemented through event-based and routine activities integrated with community social life. These activities included the commemoration of Kartini Day through the distribution of basic food packages to underprivileged community members, the sharing of iftar meals (takjil) during Ramadan, school anniversary activities involving community clean-up and social interaction, as well as routine programs such as scouting and community service. These activities were effective in enhancing students’ social awareness through direct experiential learning. However, challenges remain, particularly in the lack of systematic evaluation and the limited sustainability of the programs. This study contributes to character education and primary school management literature by demonstrating how student development programs can strengthen social awareness through community-based experiential activities.